A Study on Axial Compression Performance of Large Diameter-Thickness Ratio Concrete-Filled Gas Drainage Steel Pipe. (21st August 2021) - Liu, Zi-Lu; Ma, Zhan-Guo; Li, Ye; Gong, Peng; Li, Ke-Long; Liu, Wang
Abstract : A large number of gas drainage pipes are obsoleted in the coal mine gas drainage system, and it causes serious waste. If concrete is poured into the discarded gas drainage pipes as components for underground roadway support, it is very significant for sustainable development of mine. Therefore, it is necessary to study the mechanical properties of the concrete-filled gas drainage steel pipe. Most frequently used gas drainage pipes are spiral welded steel pipe (SSP-I) and spiral external rib steel pipe (SSP-II). In this study, three different concrete-filled steel pipes are taken as the research object: SSP-I concrete-filled steel pipes, SSP-II concrete-filled steel pipes, and RSP concrete-filled ordinary round steel pipes. Through the axial compression test, the failure mode and relationship between stress-strain of concrete-filled steel pipes were obtained. Subsequently, the ultimate bearing capacity of three types of specimens was calculated based on the unified strength theory, limit equilibrium theory, and superposition theory. The test results show that both the SSP-I concrete-filled pipe columns and RSP concrete-filled pipe have good post-peak load-bearing capacity and ductility, and the second peak load reaches 70.38% and 81.92% of the ultimate load, respectively. The load-bearing capacity of SSP-II concrete-filled pipe columns is dropped sharply after bearing ultimate load, and the second peak load reaches only 36.47% of the ultimate load. The failure characteristics of concrete-filled gas drainage pipe columns show that the core concrete is compressed to powder and explain that the gas drainage pipe has fully exerted its restraint on the concrete. The FE method was used to simulate the compression test of three types of concrete-filled steel pipes, and the numerical simulation results show good agreement with the experimental results. Theoretical calculations show that the calculation of concrete-filled gas drainage pipe columns based on the superposition theory EC4-2004 is the closest to the measured value. Therefore, the EC4-2004 standard is recommended to calculate the ultimate bearing capacity of concrete-filled gas drainage pipe columns.